THE INHIBITION ASPECTS OF ENGLISH TEACHING LEARNING PROCESS IN SMA NEGERI BENLUTU, SO’E - Billik, Marthisa Olivia (JOURNAL OF ADVANCED ENGLISH STUDIES, 2019)
The purposes of the study are to explain students’ and teachers’ experience in dealing with the inhibit aspects of English teaching-learning process. This study is used the qualitative approach and the case study as the design of the study. The participants of the study were 26 students and 3 teachers of SMA Negeri Benlutu, So'e. The results of the study shown that the inhibition aspects such as rural environment, lack of learning resources makes the students left behind in English education background. As well as the local cultural factor, it is also affects the students to use the local language more often than using English in class activity. Besides that, students’ negative attitudes also cause the students unmotivated in class. The results concluded that schools and governments should review their policies in applying English learning in a rural school environment. It is expected that teachers and students can get the solution to avoid the factors that inhibiting the effectiveness of learning English in the classroom